PROGRAM MERDEKA BELAJAR KAMPUS MERDEKA MEMBANGUN DESA/KULIAH KERJA NYATA TEMATIK PEMBINAAN KESENIAN GENDER WAYANG DI DESA ADAT KUKUB - Weda Wikantika, I Putu; Kodi, I Ketut; Adhi Santika, Sang Nyoman Gede (JURNAL DAMAR PEDALANGAN, 2025)
The rapid development of times demands students to possess skills and knowledge relevant to the issues faced by society. In this context, the "Merdeka Belajar Kampus Merdeka" (MBKM) program plays an important role as an innovative learning platform, encompassing various activities such as internships, research, and thematic Community Service (KKN). This research focuses on the Desa Membangun (Village Development) program in Kukub Traditional Village, Bali, which was once known for its art and cultural potential but is currently experiencing a decline in interest among the younger generation towards traditional arts, especially Gender Wayang. The aim of this research is to preserve the traditional art by involving the community in the learning process and the introduction of the art form. The methods used include socialization, training, and field practice. The results of this activity are expected to increase awareness and interest in the community to understand and preserve the Gender Wayang art, while also contributing to the improvement of education and culture in Kukub Traditional Village. This research demonstrates that by involving both students and the community, the preservation of traditional arts can be more effective and sustainable.